Histamine H3 Heteroreceptors Suppress Glutamatergic and GABAergic Synaptic Transmission in the Rat Insular Cortex - Takei, Hiroki; Yamamoto, Kiyofumi; Bae, Yong-Chul; Shirakawa, Tetsuo; Kobayashi, Masayuki (Frontiers in Neural Circuits, 2017)
Histamine H3 receptors are autoreceptors that regulate histamine release from histaminergic neuronal terminals. The cerebral cortex, including the insular cortex (IC), expresses abundant H3 receptors; however, the functions and mechanisms of H3 receptors remain unknown. The aim of this study was to elucidate the functional roles of H3 in synaptic transmission in layer V of the rat IC. Unitary excitatory and inhibitory postsynaptic currents (uEPSCs and uIPSCs) were obtained through paired whole-cell patch clamp recording in cerebrocortical slice preparations. The H3 receptor agonist, R-α-methylhistamine (RAMH), reduced the uEPSC amplitude obtained from pyramidal cell to pyramidal cell or GABAergic interneuron connections. Similarly, RAMH reduced the uIPSC amplitude in GABAergic interneuron to pyramidal cell connections. RAMH-induced decreases in both the uEPSC and uIPSC amplitudes were accompanied by increases in the failure rate and paired-pulse ratio. JNJ 5207852 dihydrochloride or thioperamide, H3 receptor antagonists, inhibited RAMH-induced suppression of uEPSCs and uIPSCs. Unexpectedly, thioperamide alone increased the uIPSC amplitude, suggesting that thioperamide was likely to act as an inverse agonist. Miniature EPSC or IPSC recordings support the hypothesis that the activation of H3 receptors suppresses the release of glutamate and GABA from presynaptic terminals. The colocalization of H3 receptors and glutamate decarboxylase or vesicular glutamate transport protein 1 in presynaptic axon terminals was confirmed through double pre-embedding microscopy, using a combination of pre-embedding immunogold and immunoperoxidase techniques. The suppressive regulation of H3 heteroreceptors on synaptic transmission might mediate the regulation of sensory information processes, such as gustation and visceral sensation, in the IC.